2001
DOI: 10.2527/2001.7961523x
|View full text |Cite
|
Sign up to set email alerts
|

Ileal and total tract nutrient digestibilities and fecal characteristics of dogs as affected by soybean protein inclusion in dry, extruded diets.

Abstract: Plant-based protein sources are generally less variable in chemical composition than animal-based protein sources. However, relatively few data are available on the nutrient digestibilities of plant-based protein sources by companion animals. The effects of including selected soybean protein sources in dog diets on nutrient digestion at the ileum and in the total tract, as well as on fecal characteristics, were evaluated. Six protein sources were used: soybean meal (SBM), Soyafluff 200W (soy flour), Profine F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
70
6
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 11 publications
13
70
6
7
Order By: Relevance
“…Bednar et al (2000) used various ingredients that contained protein including wheat, corn, wheat gluten meal, beef and bone meal, poultry byproduct meal, or poultry meal. Diets used by Clapper et al (2001) contained chicken bone residue next to a protein source and Gajda et al (2005) used various protein sources. Although 5 other studies were found to report apparent ileal CP and AA digestibility values in adult dogs, their data were not used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bednar et al (2000) used various ingredients that contained protein including wheat, corn, wheat gluten meal, beef and bone meal, poultry byproduct meal, or poultry meal. Diets used by Clapper et al (2001) contained chicken bone residue next to a protein source and Gajda et al (2005) used various protein sources. Although 5 other studies were found to report apparent ileal CP and AA digestibility values in adult dogs, their data were not used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The data set contained information on BW, food intake, dietary N content, and apparent fecal and apparent ileal digestibility of N. From 24 diets reported in 6 studies (Bednar et al, 2000;Clapper et al, 2001;Gajda et al, 2005;Tjernsbekk et al, 2014), apparent ileal digestibility values of individual AA were also collected. Studies where diets were used composed of only 1 protein source (e.g., soybean meal, meat meal) were excluded as these were considered to be not representative for commercial diet compositions.…”
Section: Data Used To Derive Equationsmentioning
confidence: 99%
“…O subprocessamento da soja mantém estes fatores ativos, prejudicando a obtenção de bons resultados com o alimento (Butulo, 2000). Desta forma, o baixo CDA da PB do farelo de soja encontrado por Yanka et al (2003), entre 64,3 e 68,6%, em comparação ao deste e de outros estudos (Clapper et al, 2001;Murray et al, 1997;Zuo et al, 1996), pode ser decorrente do uso de um ingrediente mal processado. Segundo Yanka et al (2003), a baixa digestibilidade registrada em seu experimento pode ser resultado do alto teor de estaquiose no farelo de soja utilizado (112 g de estaquiose por quilograma de farelo de soja).…”
Section: A B C Means Of the Same Nutrient Without A Common Letter Dunclassified
“…Embora os ingredientes proteicos de origem vegetal possuam menor variação em seu valor nutricional, quando comparado aos de origem animal, ainda são escassos estudos disponíveis com relação à digestibilidade destes para animais de companhia (CLAPPER et al, 2001). Por outro lado, a composição nutricional e a biodisponibilidade dos nutrientes das farinhas de origem animal são inconsistentes, pois são infl uenciadas, entre outros fatores, pelo nível de inclusão dos diferentes tecidos animais e pela temperatura e tempo de processamento da farinha (FAHEY & HUSSEIN, 1998).…”
Section: Introductionunclassified